Pre- and post-COVID 19 outbreak relationship between physical activity and depressive symptoms in Spanish adults with major depressive disorder: a secondary analysis of the RADAR-MDD cohort study - Ibáñez, Delia; Condominas, Elena; Haro, Josep Maria; Vázquez, Iago Giné; RADAR-MDD-Spain,; Bailón, Raquel; Garcia, Esther; Kontaxis, Spyridon; Peñarrubia-Maria, Maria Teresa; Arranz, Belen; Llaosa-Scholten, Raúl; Gardeñes, Lluisa; et al. (Frontiers in Psychology, 2024)
Aim: To evaluate the longitudinal association of sedentary behaviour, light and moderate-to-vigorous physical activity (MVPA) participation with depressive symptoms and whether their possible association changed depending on the pandemic phase. Methods: This longitudinal study conducted secondary analysis from the Spanish cohort of the Remote Assessment of Disease and Relapse – Major Depressive Disorder (RADAR-MDD) study. Depressive symptoms were assessed by the Patient Health Questionnaire (PHQ-8). Sedentary behaviour and physical activity were estimated via wrist-worn devices. Linear mixed models evaluated the longitudinal associations of sedentary behaviour and physical activity (light and moderate-to-vigorous intensities) with depressive symptoms. Results: In total, 95 participants (67.5% women, 53.0 [±10.5] years of age on average) were monitored pre-Covid-19 and included in the analyses. Pre-Covid-19, 73.7% of participants presented depression, and, on average, participated in 13.2 (±1.08) hours/day of sedentary behaviour, 2.42 (±0.90) hours/day of light physical activity and 23.6 (±19.80) minutes/day of MVPA. Considering all the observations (from November 2019 to October 2020), an additional hour/day of sedentary behaviour was longitudinally associated with higher depressive symptoms (βstd=0.06, 95% confidence interval (CI) 0.10 to 0.47), whereas an additional hour/day in light physical activity was associated with lower depressive symptoms (βstd=-0.06, 95% CI -0.59 to -0.15). Time in MVPA was not associated with depressive symptomatology. The association of sedentary behaviour and light physical activity with depressive symptoms was significant only during pre-Covid-19 and Covid-19 relaxation periods, whereas during the strictest periods of the pandemic with regards to the restrictions (lockdown and de-escalation), the association was not observed. Conclusions: Sedentary behaviour and light physical activity were longitudinally associated with depressive symptoms in participants with a history of MDD. The incorporation of light physical activity should be stimulated in adults with a history of MDD. Neither sedentary behaviour nor light physical activity were associated with depressive symptoms during the most restrictive COVID-19 phases, whereas sedentary behaviour (positively) and light physical activity (negatively) were associated with depressive symptoms in persons with MDD before and after the COVID-19 pandemic.